INTEGRATION OF EMPLOYEE PERFORMANCE, SERVICE QUALITY, ARTIFICIAL INTELLIGENCE, AND SOCIAL MEDIA IN INCREASING PATIENT NUMBERS: A SYSTEMATIC LITERATURE REVIEW - Irawan, Beny; Mochklas, Mochamad; Haksama, Setya (Journal of Public Health Science, 2025)
This literature review analyzes and synthesizes the relationship between employee performance, service quality, the use of artificial intelligence (AI), and the use of social media in efforts to increase patient numbers in the healthcare sector. Using a systematic literature review approach, this research examines various studies that discuss the contribution of each variable to increasing patient accessibility and interest. A total of 20 empirical journal articles published between 2018 and 2024 were analyzed thematically. Data were collected from various academic databases using keywords such as "employee performance," "service quality," "number of patients," "patient volume," "artificial intelligence in healthcare," "social media in healthcare," "patient acquisition," and "patient retention." Most of the reviewed studies used quantitative methods, applying statistical tools such as linear regression analysis. The results indicate that social media and AI influence performance and the number of visits. This review highlights the need for healthcare facilities to utilize social media and AI to improve employee and patient performance. Future research should explore the relationship between social media and AI, as the digital era challenges every organization to be more creative and innovative in order to stay up-to-date